Bitcoin and Digital Currency: Difficulties, Open Doors and Future Works - Alfian, Sulthan Taqi Sampoerna; Ichsanudin, Fathur; Mulyati; Ndruru, Natalia (Blockchain Frontier Technology, 2022)
Bitcoin and other conspicuous digital forms of money definitely stand out enough to be noticed since the most recent quite a while. All around the world known as advanced coin and virtual cash, this cryptographic money is acquired and exchanged inside the blockchain framework. The blockchain innovation taken on in utilizing the digital currency has caused a stir inside the financial area, government, partners and individual financial backers. The ascent of the cryptographic money inside this long time starting from the beginning of Bitcoin in 2009 has surprised the market. Cryptographic money is expected as the future cash that would supplant the ongoing paper money around the world. Despite the fact that the interest has grabbed the eye of clients, many don't know about its chances, disadvantages and difficulties for what's to come. Explores on cryptographic forms of money are as yet missing nevertheless at its outset stage. In giving significant aid and view to the scholarly field and clients, this paper will examine the valuable open doors in digital money, for example, the security of its innovation, low exchange cost and high venture return. The inventiveness of this paper is on the conversation inside regulation and guideline, high energy utilization, probability of crash and air pocket, and goes after on network. The future endeavors of cryptographic money and its application will be methodically evaluated in this paper.